PENANAMAN NILAI KEPAHLAWANAN DALAM PENDIDIKAN DENGAN MEMANFAATKAN DATA SEJARAH - Moh. Rosyid (Jurnal Forum Tarbiyah, 2012)
Timescales experienced by founding fathers in establishing and enforcing the country from the clutches of invaders if not immediately bedocumented is feared to be forgotten its heroism spirit by that current and future generations. Heroism will be remembered by the present and future generations if understood the heroic story. Embedding heroism can be imperishable whenteachers of history provide a fun and dynamic method of learning. The dynamics of teaching  is something that should receive extra attention without which  learning process will be boring. A practical solution, teacher  should be experts in the field of study not just anybody. This  may eliminate the impression that learning history is merely memorizing events and forgetting the incident analysis. Embedding heroism in education can utilize historical data. It is expected to develop a sense of nationalism and nationhood, rectifying historical data, memorizing national heroes who are sometimes forgotten by the hustle oflife, and historical data can be used as authentic evidence before the tribunal. Scattered historical data still needs to be explored by promoting historical source criticism to avoid victimization history in the next  generation. It is to be anticipatedas historical data may be used as weapons strengthen the regime inpower, even it can be used as bullets to kill political rivals.